Pertumbuhan Anak Usia Dibawah 5 Tahun yang Tinggal di Tempat Pembuangan Akhir Sampah dan Kondisi Sanitasi Lingkungannya - Erika, Kadek Ayu; Aprilia Dwi Aryanti; Suni Hariati (Jurnal Yoga dan Kesehatan, 2026)
Less than optimal development of children under 5 years of age can be caused by one factor is inadequate environmental sanitation, especially in landfills sites. This study aims to determine the growth of children under 5 years of age and the environmental sanitation of those living in the landfill sites. This research uses descriptive analytics with purposive sampling technique. The number of samples in this study were 91 parents who had children under 5 years of age in landfills sites. The research instruments used weight measurement tools, namely the RGZ-20 baby scale (0-2 years) and digital foot scales (2-5 years). Height was measured using an infantometer/length board/microtoise onemed, and head circumference was measured using a Medline and recorded on an anthropometric measurement questionnaire. Data were presented in frequency distributions of demographic characteristics, growth of children under 5 years of age, environmental sanitation, and cross-tabulations between variables. Growth based on infant characteristics showed nutritional status BB/U 36 (75%), BB/TB 21 (48.8%), and LK/U 31 (72.1%) in the normal category according to age. However, most were in the stunting index (19, or 39.6%) and waste disposal facilities were categorized as very poor. Environmental sanitation conditions at the landfill sites included drinking water sources from boreholes/pumps (27.5%); available, watertight, and uncovered waste bins (51.6%); use of septic tanks (100%); and no sewerage available (49.5%). Parents who use borehole/pump water sources, trash bins that are not watertight and uncovered, and have no sewerage in the landfill sites where they live have children under 5 years of age with normal growth.